1998
DOI: 10.2166/wst.1998.0239
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale SBR and MF operation for the removal of organic and nitrogen compounds from greywater

Abstract: A pilot plant of SBR (Sequencing Batch Reactor) and MF (microfiltration) process was operated in order to treat and reuse the greywater produced from an office building. The performance of SBR for greywater was satisfactory as the effluent had 20 mg/l, 5 mg/l, and 0.5 mg/l of SCOD, BOD, and ammonia, respectively. The cyclic operation of SBR used in this study proved more effective in nitrification and denitrification than the conventional SBR operation. However, the most effective mode was step-feed SBR for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The TKN removal efficiency of both the SBR and MSBR systems was increased with an increase in HRT or decrease in organic loading because the increase in HRT or decrease in organic loading resulted in increasing the population of nitrification bacteria due to the increase in the sludge age or SRT (Metcalf & Eddy, 1991;Gebara, 1999;Irvine and Busch, 1979;Shin et al, 1998;Helmer and Kunst, 1998). The TKN was removed by both assimilation and nitrification mechanisms in the MSBR reactor (Sirianuntapiboon and Tondee, 2000;Shin et al, 1998;Keller et al, 1997;Kagi and Uygur, 2002). However, the MSBR system showed a higher TKN removal efficiency than the SBR system because the total bio-sludge mass of the MSBR was higher than that of the SBR system.…”
Section: Discussionmentioning
confidence: 99%
“…The TKN removal efficiency of both the SBR and MSBR systems was increased with an increase in HRT or decrease in organic loading because the increase in HRT or decrease in organic loading resulted in increasing the population of nitrification bacteria due to the increase in the sludge age or SRT (Metcalf & Eddy, 1991;Gebara, 1999;Irvine and Busch, 1979;Shin et al, 1998;Helmer and Kunst, 1998). The TKN was removed by both assimilation and nitrification mechanisms in the MSBR reactor (Sirianuntapiboon and Tondee, 2000;Shin et al, 1998;Keller et al, 1997;Kagi and Uygur, 2002). However, the MSBR system showed a higher TKN removal efficiency than the SBR system because the total bio-sludge mass of the MSBR was higher than that of the SBR system.…”
Section: Discussionmentioning
confidence: 99%
“…Graywater originating from laundries has demonstrated varying levels of alkaline pH: for example, reported values were in the range 8-10 (Eriksson et al 2002), 9.3-10 (Christova-Boal et al 1996, 8.1 (Surendran & Wheatley 1998), and 9.3-9.5 (Dixon et al 1999a). However, Shin et al (1998) and Friedler (2004) reported graywater pH from laundries as close to neutral (i.e., 6.3-7.4 and 7.5, respectively). The pH of graywater is generally in the alkaline range of the pH scale, and thus the findings from these two studies may have resulted from the use of pH-balanced detergents in laundries.…”
Section: Chinese Journal Of Population Resources and Environment 253mentioning
confidence: 96%
“…There is some research on the quality of greywater and its variation by source (Tables 1 and 2) and within source type (Matos, 2009;Matos et al, 2010). For instance, literature reports important differences for washing machines between the effluents of different cycles and the same can be expected from dishwashers (Rose et al, 1991;Burrows et al, 1991;ChristovaBoal et al, 1996;Surendan& Wheatley, 1998;Shin et al, 1998;Nolde, 1999;Eriksson et al, 2002;Friedler, 2004 49-69 (4) 102* (2) 50-210 (1) 108 (2) 14-296 (3) Total solids (mg/L) 631 (2) 777-1090 (5) 250 (6) 558 (2) 835 (5) 1272-2410 (5) 2410 (6) 658 ( 459-670 (5) 670 (6) 97-106 (5) 69-170 (6) 97 (7) 10-424 (5) 370 (6) pH 6.4-8.1 (1) 7.1 (5) 7.6 (2) 6.7-7.4 (4,5) 8.1 (2) 7.0-8.1 (5) 6.5 (5) 6.3-7.4 (8) 9.3-10. Christova-Boal et al (1996); (2) Surendran& Wheatley (1998); (3) Rose et al (1991); (4) Burrows et al (1991); (5) Friedler (2004); (6) Siegrist et al (1976); (7) Almeida et al (1999); (8) Shin et al (1998);(9) Nolde (1999); (10) Laak (1974) ; (11) …”
Section: Greywater Characteristics 211 Quality Parametersmentioning
confidence: 99%
“…* Siegrist et al, (1976);Christova-Boal et al, (1996); Burrows et al, (1991); Rose et al, (1991); Shin et al, (1998);Almeida, et al, (1999);NUEA (2001);Friedler (2004).…”
Section: Total Greywater and Light Greywater Qualitymentioning
confidence: 99%